The obesity paradox in intracerebral hemorrhage: a systematic review and meta-analysis - Wang, Zexu; Wang, Jie; Wang, Jiayan; Liao, Yinghua; Hu, Xin; Wang, Manni (Frontiers in Endocrinology, 2023)
Background Intracerebral hemorrhage (ICH) has a mortality rate which can reach 30-40%. Compared with other diseases, obesity is often associated with lower mortality; this is referred to as the 'obesity paradox'. Herein, we aimed to summarize the studies of the relations between obesity and mortality after ICH. Method For this systematic review and meta-analysis (PROSPERO registry CRD42023426835), we conducted searches for relevant articles in both PubMed and Embase. Non-English language literature, irrelevant literature, and non-human trials were excluded. All included publications were then qualitatively described and summarized. Articles for which quantitative analyses were possible were evaluated using Cochrane's Review Manager. Results Ten studies were included. Qualitative analysis revealed that each of the 10 studies showed varying degrees of a protective effect of obesity, which was statistically significant in 8 of them. Six studies were included in the quantitative meta-analysis, which showed that obesity was significantly associated with lower short-term (0.69 [0.67, 0.73], p<0.00001) and long-term (0.62 [0.53, 0.73], p<0.00001) mortality. (Data identified as (OR [95%CI], p)) Conclusion Obesity is likely associated with lower post-ICH mortality, reflecting the obesity paradox in this disease. These findings support the need for large-scale trials using standardized obesity classification methods.